Training and effective attitude in the prevention of drug abuse and stimuli among the recipients of the educational reform centers of the country - Hajargasht, Hamed; Zamani Moghadam, Afsaneh; Shaban Nejad, Reza (Researcher Bulletin of Medical Sciences, 2019)
The purpose of this study is to present an effective education model and approach to drug abuse prevention among educational clients and improvement centers of the country. This srudy is a descriptive and surveying research and the combination method (qualitative and quantitative). The Delphi panel has 22 experts with a history of coaching and 212 employees at the correctional center. The data gathering tool was a semi-structured interview and a researcher-made questionnaire. To determine the content validity of the questionnaire, experts judgment and comprehensive literature review of the research have been used. For reliability measurement, Cronbach's alpha coefficient was used, which was obtained at 981. For data processing and statistical analysis, SPSS-23 software was used. In addition to descriptive statistics, the correlation coefficient test, exploratory factor analysis has been used. Findings show that the most effective component in the knowledge aspect of drug abuse prevention and stimulus among the clients of the correctional centers of the country in desirable condition, knowledge of the laws and regulations (8.8019), health and safety (8.7869), cognitive (8.7764) and religious and spiritual (8.6962). In the aspect of attitude, the confidence is (8.7453) and emotional (8.7022) respectively. Also, the results show that there is a significant difference between the current and the desired status in the field of health, religious and spiritual, legal awareness, cognitive, emotional and self-confidence of the recipients.